Evaluation of solid oxide fuel cell performance with anode recirculation using variable flow ejector at rated conditions - Soumei BABA (The Japan Society of Mechanical Engineers, 2015)
An anode gas recycle (AGR) system that uses an ejector for a 1 kW solid oxide fuel cell (SOFC) was developed to increase the electrical efficiency of combined power generation. The effects of anodic recirculation on the SOFC performance were determined experimentally with a variable flow ejector at a fuel utilization of 0.80 to 0.87 and a steam feed rate of 0 to 1.5 g/min. A quadrupole mass spectrometer was used to identify the recirculation ratio, the gas composition of reformed gas at the SOFC inlet, and that of the recycle gas at the recycle plenum located downstream of the SOFC. The recirculation ratio could be changed from 0.67 to 0.71 by moving the needle inside the ejector nozzle, and thus the SOFC showed stable performance with no steam supply, due to the large recirculation ratio of steam produced via the electrochemical reaction that was supplied to the injected fuel for the steam reforming process. The results indicate a slight decline in output power with an increase in the recirculation ratio. In addition, the fuel utilization limitation for SOFC operation is estimated to be as much as that for a one-path SOFC system without AGR to avoid a local lack of hydrogen as fuel.